Evaluation of automated chromosome G-band images enhancement using histogram equalization - Wayalun, Pichet; Wanchanthuek, Phatthanaphong; Songram, Panida; Chompoowises, Phatthanaphong; Laopracha, Natthariya (Asia-Pacific Journal of Science and Technology, 2017)
This paper presents analysis of evaluation chromosome image enhancement. It has been appeared in literature that there are 4 different techniques, i.e. Contrast Limited Adaptive Histogram Equalization, Contrast Stretching, Histogram Equalization and Mathematical Morphology, on chromosome image type G-BAND. From our study, We found that Histogram Equalization give promising results in enhancement. A success rate of 93.32% has been achieved.